Conflict as a Catalyst for Innovation in Organizations: How to Optimize it in a Collectivism Culture Setting? - Wahyu, Agung Minto; Purba, Debora E. (Jurnal Manajemen dan Inovasi (MANOVA), 2026)
Objective – Conflict is inevitable in organizations. Conflict can be a catalyst for innovation in the organization. This study aims to review the types of conflict, conflict management styles, and other supporting factors that can stimulate the innovation in organizations in the setting of collectivism culture. Design/methodology/approach – The method used is a narrative review of secondary data, involving the analysis of 17 articles, most of which are of high quality (indexed in Scopus Quartiles 1–2). The available literature sources were then analyzed and synthesized into meaningful information in accordance with the research objectives. Findings – The findings show that cognitive conflict (also called task conflict) type can stimulate innovation in the organization, while affective conflict (also called relationship conflict) type is the opposite. Conflict management styles that are relevant in collectivism work culture in producing innovation are integrating, compromising, and obliging. For obliging, another critical success factor is that one of the parties to the conflict has a lower bargaining position. Research limitations/implications – The majority of the literature cited in this study is derived from research conducted in China. Although China and Indonesia share a collectivistic cultural orientation, caution is warranted when applying these findings to the Indonesian context. Practical implications – Organizations are expected to manage (cognitive) conflict at an appropriate level in order to stimulate innovation. Therefore, leaders need to develop strategies that involve a variety of programs to achieve this. Originality/value – This study contributes by conclusively demonstrating, based on a variety of existing research, that conflict should not be viewed solely in a negative light; rather, well-managed conflict can catalyze innovation.